Supportive care of women with breast cancer: key concerns and practical solutions. Issue 10 (21st November 2016) - Zdenkowski, Nicholas; Tesson, Stephanie; Lombard, Janine; Lovell, Melanie; Hayes, Sandra; Francis, Prudence A; Dhillon, Haryana M; Boyle, Frances M
Summary: Patients diagnosed with breast cancer may have supportive care needs for many years after diagnosis. High quality multidisciplinary care can help address these needs and reduce the physical and psychological effects of breast cancer and its treatment. Ovarian suppression and extended endocrine therapy benefits are associated with vasomotor, musculoskeletal, sexual and bone density‐related side effects. Aromatase inhibitor musculoskeletal syndrome is a common reason for treatment discontinuation. Treatment strategies include education, exercise, simple analgesia and a change to tamoxifen or another aromatase inhibitor. Chemotherapy‐induced alopecia may be a constant reminder of breast cancer to the patient, family, friends, acquaintances and even strangers. Alopecia can be prevented in some patients using scalp‐cooling technology applied at the time of chemotherapy infusion. The adverse impact of breast cancer diagnosis and treatment on sexual wellbeing is under‐reported. Identification of physical and psychological impacts is needed for implementation of treatment strategies. Fear of cancer recurrence reduces quality of life and increases distress, with subsequent impact on role functioning. Identification and multidisciplinary management are key, with referral to psychosocial services recommended where indicated. The benefits of exercise include reduced fatigue, better mental health and reduced musculoskeletal symptoms, and may also include reduced incidence of breast cancer recurrence. Identification and management of unmet supportive care needs are key aspects of breast cancer care, to maximise quality of life and minimise breast cancer recurrence.